Pelatihan Peningkatan Pemahaman Penggunaan Facebook dan Instagram pada Kelompok Petani Vanili dalam Penyebaran Informasi Pertanian - Gede Surya Mahendra; I Putu Yoga Indrawan; Putu Gede Surya Cipta Nugraha (Universitas Pahlawan Tuanku Tambusai, 2022)
Vanilla (Vanilla planifolia) has a high price due to the complicated cultivation and harvesting process, which is also faced by PKM partners. The Balinese vanilla farmer group has started to recover from the slump that almost 10 years of vanilla production in Bali was attacked by stem rot pests. The purpose of this PKM activity is to provide training to PKM Partners on the use of social media in disseminating information about the vanilla plant. The stages of PKM activities include the stages of identification, preparation, implementation, monitoring and evaluation as well as reporting and publication. PKM activities will be held on 27 June 2021 and 5 July 2021 with a focus on training on the use of Facebook and Instagram. This PKM activity was attended by 6 vanilla farmers. Based on the pretest and posttest, there was an increase in knowledge from the previous pretest value of 42.74%, in the posttest it increased to 75.24%. PKM activities have been successfully implemented and achieved in good conditions.